2005
DOI: 10.1177/104990910502200410
|View full text |Cite
|
Sign up to set email alerts
|

Humor in hospice care: Who, where, and how much?

Abstract: Humor has been identified as an intrinsic social phenomenon occurring in all groups throughout human history. It is among the most prevalent forms of human social behavior yet one of the least understood or defined. Although researchers in a number of disciplines have studied the effects of humor on patients, limited work has focused on end-of-life care. The present study investigated social interactions involving humor in hospice settings using nonparticipant observation. Results revealed that humor was prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 22 publications
2
41
0
4
Order By: Relevance
“…They concluded that humour is used to facilitate communication and avoid conflict. In a further study humour use in a hospice setting was studied, highlighting that humour was present in 85% of interactions and was patient‐initiated 70% of the time (Adamle & Ludwick 2005).…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that humour is used to facilitate communication and avoid conflict. In a further study humour use in a hospice setting was studied, highlighting that humour was present in 85% of interactions and was patient‐initiated 70% of the time (Adamle & Ludwick 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Both family caregivers and patients express humor and distress, consistent with the literature indicating the dying process can be a time of both joy and sadness. [32][33][34] It is difficult to compare how hospice nurse communication compares to other end-of-life encounters, because little research has been conducted in this area. Timmerman and colleagues 35,36 applied RIAS to initial palliative care consultation sessions with radiation oncologists.…”
Section: Description Of Home Hospice Visit Dialoguementioning
confidence: 99%
“…As a complementary therapy and intervention technique, therapeutic humor has been used in numerous areas, including end of life (Adamle & Ludwick, 2005), oncology (Christie & Moore, 2005), critical care (Leiber, 1986), women's health (Ragan, 1990), psychological settings (Richman, 1996), and the emergency room ( van Wormer & Boes, 1997). The use of humor as a coping mechanism is well supported in the literature (Nezlek & Derks, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A review of nursing literature (Adamle & Ludwick, 2005;Du Pre, 1998;Robinson, 1991;Wooten, 2005) shows that humor in the context of culture to reach positive therapeutic outcomes in delivering care and avoid its misuse has received limited attention. This research study builds on the phenomenon of humor from a cultural perspective by examining nursing faculty teaching practices and viewpoints of therapeutic humor in two different countries, the United States and Taiwan.…”
Section: Introductionmentioning
confidence: 97%